2014
DOI: 10.1182/blood-2013-10-532671
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a permissible HLA mismatch in hematopoietic stem cell transplantation

Abstract: Key Points Mismatches in alleles C*03:03/C*03:04 were most frequent (68.7%) among the transplants with a single allele level mismatch in HLA-C. The 7/8 C*03:03/C*03:04 mismatch group was not significantly different from the 8/8 HLA matched transplants in any transplant outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 43 publications
(66 reference statements)
8
64
0
2
Order By: Relevance
“…Thus, allele mismatches differ from antigen mismatches in the degree of sequence similarity 3,5 and in expression levels, and these features may contribute to the historically lower risks of allele compared with antigen mismatches. These results are consistent with recent studies demonstrating that the HLA-C*03:03/03:04 mismatch is a well-tolerated highfrequency mismatch 24,25 and provide a potential mechanism (ie, low expression) for why this particular mismatch is permissive.…”
Section: Model 1: Allele and Antigen Mismatchessupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, allele mismatches differ from antigen mismatches in the degree of sequence similarity 3,5 and in expression levels, and these features may contribute to the historically lower risks of allele compared with antigen mismatches. These results are consistent with recent studies demonstrating that the HLA-C*03:03/03:04 mismatch is a well-tolerated highfrequency mismatch 24,25 and provide a potential mechanism (ie, low expression) for why this particular mismatch is permissive.…”
Section: Model 1: Allele and Antigen Mismatchessupporting
confidence: 82%
“…6,7,24,25 Restriction of the study population to pairs with only 1 HLA-C mismatch removes any contribution of disparity at other HLA loci and addresses whether, among the spectrum of HLA-C mismatches, there are combinations of mismatches that are better tolerated than others.…”
Section: Study Population Hla and Mfimentioning
confidence: 99%
“…28 Furthermore, an initial observation that HLA-B and -C incompatibilities were better tolerated than -A or -DRB1 mismatches 11 has not been confirmed in more recent studies. 5,29 In their latest report Morishima et al 15 provided evidence that single HLA-A, -B or -C allele mismatches and double HLA-DRB1/DQB1 mismatches are associated with increased mortality in non-T-cell-depleted bone marrow transplantation. Interestingly single HLA-DRB1, -DQB1 or -DPB1 mismatches did not significantly affect overall survival rate.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 99%
“…18,20 However this could possibly be explained by the very high frequency (68.7%) of C*03:03/03:04 mismatches in the NMDP study. 29 This incompatibility had previously been reported to be more permissive, on the basis of in vitro assays measuring direct cytotoxic T-lymphocyte alloreactivity.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 99%
“…The risk of transplant-related immunological events may vary according to patient-donor mismatching HLA locus, [1][2][3][4] mismatching specific HLA epitopes, 5,6 and specific mismatch combinations. 7 Furthermore, several studies have demonstrated that specific individual HLA genotypes may also affect transplant outcome, [8][9][10][11][12] although the results are not always consistent.…”
Section: Introductionmentioning
confidence: 99%